Electrical properties of La modified SrBi4Ti3.975Zr0.025O15 ceramics - Mamatha, B. (Physics and Chemistry of Solid State, 2026)
Polycrystalline Sr(Bi4-xLax)(Ti3.975Zr0.025)O15 (x = 0.025, 0.05 ,0.075 and 0.1) is prepared by solid-state method. It was characterized by X-Ray Diffraction (XRD), Scanning Electron Micrograph (SEM) and Energy Dispersive Spectra (EDS). From XRD and SEM analysis, phase formation is identified and particle size is calculated. Compositions are confirmed from EDS spectra. The dielectric, ferroelectric and piezoelectric studies are investigated. Remnant polarization (Pr) is found to increase, Curie temperature (Tc) and dielectric constants are found to be decreased, and electromechanical coupling coefficients and piezoelectric charge coefficients are found to be increased as the concentration of La increases